Effectiveness of Nonpharmacological Cooling Therapy on Body Temperature Stability of Pediatric Patients with Hyperthermia: Literature Review - Ikalia Ulandari; Sendy Glaudia Dede Tule; Laila Alfida Yahya; Masriati Nabila; Fathir Bayu Pratama; Ni Wayan Wiwin Asthiningsih (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Hyperthermia in pediatric patients is a condition in which body temperature exceeds normal limits which can be caused by infection, inflammatory responses, or environmental factors. This condition requires quick and appropriate treatment to prevent complications such as seizures, fever and organ damage. This literature review aims to analyze the effectiveness of nonpharmacological cooling therapy on the body temperature stability of pediatric patients with hyperthermia. The method used is in the form of literature studies using sources or references in the form of national and international journals. The results of the literature review show that there are several effective nonpharmacological cooling techniques that help reduce the body temperature of pediatric patients with hyperthermia, namely evaporative cooling techniques, cooling baths, tepid sponge water, and oral cooling. These techniques work through the mechanism of evaporation, conduction, and body heat exchange so that they can help maintain the stability of the patient's body temperature. The conclusion of this review is that non-pharmacological cooling therapy can be used as an independent intervention or nursing action in helping to reduce and maintain body temperature stability in pediatric patients with hyperthermia.